Marinesco-Sjogren Syndrome and SIL1 Mutations - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Aachen University, Germany, and multiple centers in Europe, UK, USA, Turkey and Argentina, report the results of SIL1 mutation analysis in 62 patients presenting with early-onset ataxia, cataracts and myopathy, the characteristic Marinesco-Sjogren syndrome triad.